¿Puede Asia convertirse en el polo de las relaciones sur-sur? El mito de la recuperación liderada por el Asia - Quintos, Paul (2024)
The capitalist system has entered in a deep systemic and civilizing crisis, the worst in terms of magnitude and significance after The Big Depression, marked by poverty, hunger and unemployment due to environmental degradation. lnto this dark context, Asia has appeared like the light. The capital question is if Asia could become the dynamic center in order to help the recovery of the global system. Asia growth is, however, an illusion. Not counting China and India, the region decreased in a 0.6%. A bigger deceleration is predictable in the near future, and there are four huge seriousness problems in the long range: ( 1) persistent multidimensional and generalized poverty; (2) growing inequities; (3) environmental degradation; and (4) demographic change.